Productivity, profitability and soil biochemical properties in maize (Zea mays) and soybean (Glycine max) intercropping as influenced by population proportion of component crops - TELKAR, S G; SINGH, A K (The Indian Journal of Agricultural Sciences, 2023)
A field experiment was conducted during kharif 2016 at College of Post Graduate Studies (CAU-Imphal), Umiam, Meghalaya to study the effect of population proportions of component crops on performance of maize (Zea mays L)+ soybean [Glycine max (L.) Merr.] intercropping. The experiment was laid out in randomized block design with three replications comprised eight treatments (sole maize, sole soybean and six treatments on maize+soybean intercropping with different population proportion of component crops. Treatment 2:2 paired maize+soybean recorded maximum maize equivalent yield (3.91 t/ha) and land equivalent ratio (1.23) which were at par with intercropping treatments 1:1 Additive, 1:1 Replacement, 2:1 Replacement and 2:1 Additive but significantly higher over the sole maize and 2:1 Paired intercropped treatments. However, maximum net return (rupees 23643/ha)and B: C (1.68) ratio were recorded from 1:1 R maize+soybean which were at par with 2:1 Replacement and 2:2 Paired but significantly higher over sole maize and other intercropping treatments. Introduction of soybean as an intercrop in maize left relatively higher amount of soil available N, P, soil microbial biomass carbon (SMBC) and dehydrogenase activity (DHA) in soil after crop harvest as compared to sole maize.Significantly higher soil available N was recorded from the treatment 1:1 Replacement while significantly higher soil available P, SMBC and DHA were recorded from the treatment 2:2 Paired over sole maize, respectively.